Latinx perceptions of Spanish in Miami: Dialect variation, personality attributes and language use. (July 2019) - Callesano, Salvatore; Carter, Phillip M.
Abstract: This study examines the ways in which Cuban, Colombian, and Peninsular Spanish in Miami-Dade County (MDC) are conceptualized by Latinx participants in terms of implicit perceptions. We examine how Latinx college students – all residents of Miami – perceive Spanish language variation in Miami and predict putative differences in two domains: 1) personality characteristics related to warmth and competence traits (e.g., friendliness and intelligence), and 2) differences in usage and maintenance of Spanish. Data were analyzed for significance using a three by four within-subjects ANOVA with a series of specific statistical contrasts. Results show effects of both the language variety alone as well as interaction effects between the dialects and labels indicating ostensible family origin information. Highlights: Speaker from Spain rated higher than Colombian and Cuban speakers for competence traits. No significant difference among Cuban, Colombian, and Spanish speakers for warmth traits. Colombian speaker perceived as more likely to use English and speak English with children. Colombian and Peninsular voices ranked significantly higher than Cuban voice for physical attractiveness.